INFORMASI INTELLECTUAL CAPITAL DALAM LAPORAN ANALIS SEKURITAS: BERMANFAATKAH BAGI INVESTOR? - C. Erna Susilawati (Jurnal Keuangan dan Perbankan, 2013)
The role of intellectual capital to increase value of the firm, prompting securities analyst to include informationabout that into securities analyst report. The value of analyst report explored by previous researchers. However,information about intellectual capital in securities analyst report is not widely studied. The purpose ofthis research to investigate the value of intellectual capital information in the securities analyst report forinvestor and tries to explore the role of securites analyst to reduce asymmetry information. The result showedthat intellectual capital information used by investor and thus effects the trading volume. The other findingsshow that intellectual capital information reinforces the influence of the revision of stocks recommendation totrading volume. Abnormal return of stock when the analyst reports contain intellectual capital information ishigher than that do not contain such information.